New records and geographical distribution of ctenid spiders (Araneae: Ctenidae) in Colombia (2013)
This study provides new records, geographical distribution extensions and a checklist of the current ctenids species in Co-lombia based on the review of four arachnological collections and published literature. A total of 15 new records for Cteni-dae in Colombia are reported; nine of these species are new records for the country and the distribution of the remaining six is expanded. The genus Centroctenus Mello-Leitão, 1929 (C. ocelliventer Strand, 1909) is recorded for first time in Colombia and Cupiennius coccineus (F.O. Pickard-Cambridge, 1901) for South America. Due to the strategic geographic position of Colombia, which is a transition zone between Southern and Central American biotas, species inventories in different localities are important to fill distributional gaps. The number of known species of ctenids in Colombia is in-creased from 16 to 25 and these data will be useful for future studies in taxonomy, systematics and biogeography of this family.